Effectiveness of School-Based Video-Assisted Health Education Program on Mosquito-Borne Disease among Upper Primary Children - Dsouza, Renita Priya; Rodrigues, Devina E; Saldanha, Prakash M (Journal of Health and Allied Sciences NU, 2022)
Introduction Malaria and dengue fever are the two major mosquito-borne diseases (MBD) seen in India and these diseases are endemic in many of the Indian states. Educating the public is one of the effective ways to prevent any diseases and school children act as health messengers to their family members. Video-assisted teaching methods help the children to understand the concept better and grasp it easily. The aim of the study was to assess the effectiveness of school-based video-assisted health education on knowledge regarding MBD.Materials and Methods The study design used was cross-sectional one group pre- and posttest design. Ninety-five children studying in 6th and 7th standard of two higher primary schools located in a rural area of southern India have participated in the study. The knowledge level of the children was assessed using a structured knowledge questionnaire before and after the video-assisted health education program. Children were educated using PowerPoints and videos in three sessions on various aspects of MBD.Statistical Analysis Data was analyzed using a statistical software, SPSS-23. Descriptive and inferential statistics were used to analyze the data.Results The mean score was 23.58 ± 7.08 in the pretest and the posttest mean score was 53.01 ± 3.90. The minimum score was 13 in the pretest and in the posttest it was 44 with a maximum possible score of 60. Intervention was effective and led to 49.05% of gain in knowledge of children from pretest to the posttest and the difference in the mean value was statistically significant (t = 36.58, p < 0.001).Conclusion Even though children had the knowledge on MBD, it was not adequate and video-assisted health education was useful to improve their knowledge. More consistent efforts are needed to educate the children on different health issues using various sense stimulating teaching aids to help them develop into healthy future generation.
Keywords: dengue; health education; malaria; mosquito-borne diseases; school children; video-assisted